Changes and mechanisms of apparent resistivity before earthquakes of MS6.0–6.9 on the Chinese mainland - Xie, Tao; Han, Ying; Ye, Qing; Xue, Yan (Frontiers in Earth Science, 2023)
China has been conducting fixed continuous apparent resistivity observations since 1967. Up to June 2022, 45 earthquakes with magnitudes of MS6.0–6.9 have occurred within a range of approximately 250 km from normal operating stations. Through literature investigation and data analysis, monitoring stations counted 61 short-medium-term apparent resistivity anomalous changes (i.e., 44 decrease changes, 15 increase changes, and 2 perturbance changes) appearing before 39 of these earthquakes. In this study, we utilize a fault virtual dislocation model to understand the relative deformations around the epicenters before these earthquakes. The comparison results showed that 36 of the 44 decrease changes were in areas with compression enhancement and that 9 of the 15 increase changes were in areas with relative dilatancy. The results from rock petrophysical experiments and the resistivity model of the cracked medium showed decreased changes in the resistivity of water-bearing geomaterials during the successive loading of compressive stress, while the resistivity showed increased changes during the stress unloading process. Moreover, 45 of the 61 apparent resistivity anomalies were consistent with the mechanism of resistivity change under stress. These apparent resistivity anomalous changes before earthquakes may be related to the seismogenic processes such that the resistivity change is caused by medium deformation.